2016
DOI: 10.9734/bjpr/2016/19971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Extract of Unripe Annona muricata (l.) Fruits on the Haematological and Histopathological Parameters in Swiss Albino Rats Infected with Salmonella typhi

Abstract: Background: In addition to the problems of resistance to commonly used antibiotics, toxicity depicts the state of adverse effects caused by the interaction of toxicants with cells. Similarly, blood components are exposed to significant concentrations of toxic compounds as they form the medium for their transport. Aims: To study the effects of ethanol extract of unripe Annona muricata fruits on the haematological and histopathological parameters in Swiss albino rats infected with Salmonella typhi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 11 publications
7
9
1
Order By: Relevance
“…On the other hand, the administration of GE had a therapeutic effect on the liver architecture for rats before and after MSG treatment. Such findings are comparable to those of [101]. The involvement inhibits cyclo-oxygenase 2 of tannins in GE and acetogenin [102,103].…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the administration of GE had a therapeutic effect on the liver architecture for rats before and after MSG treatment. Such findings are comparable to those of [101]. The involvement inhibits cyclo-oxygenase 2 of tannins in GE and acetogenin [102,103].…”
Section: Discussionsupporting
confidence: 82%
“…The filtrates were vaporized to dryness using rotary evaporator and subsequently lyophilized to remove the extracting solvent. The crude extracts obtained was preserved in a sterile container and stored in the refrigerator at 4ºC until when ready for use [1]. The crude extracts which were obtained were sterilized using 0.45 µm millipore membrane filter in order to remove any contaminant that might be present before subsequent use.…”
Section: Extraction Of a Muricata Barkmentioning
confidence: 99%
“…Different plants and their parts are used all over the world for various purposes. Study reported that plants have an efficient constituents which are mostly used as antioxidant, antibacterial, antifungal, antiulcer, anti-inflammatory, antiviral and anticancer agents [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different plants and their parts are used all over the world for various purposes [3]. Some of which have their constituents and therapeutic properties established scientifically many others are yet to be subjected to investigations.In northern Nigeria variety of plant species are used in diseases management or no consideration to toxicological profile of the plant [4].…”
Section: Introductionmentioning
confidence: 99%